2023
DOI: 10.1590/1518-8345.6315.3885
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression, anxiety and stress in health students and impact on quality of life

Abstract: Objective: to evaluate the association between quality of life and presence of symptoms of depression, anxiety, and stress in college students in the health area. Method: cross-sectional study that included 321 students from undergraduate courses in the health area. Quality of life was measured using the World Health Organization scale, abbreviated version, in the physical, psychological, social relations and environment domains, and symptoms were assessed by the depression, anxiety and stress scale. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
4
0
2
Order By: Relevance
“…Uma revisão de escopo mostrou que o maior comprometimento da qualidade de vida estava relacionado à demora no diagnóstico da doença, às reações hansênicas, incapacidades físicas, dor neuropática e estigma (Barcelos et al, 2021). Outro estudo avaliou a associação entre qualidade de vida e presença de sintomas de depressão, ansiedade e estresse em estudantes universitários da área da saúde, evidenciando que tais sintomas mostraram-se prevalentes e com impacto negativo na qualidade de vida dos estudantes, principalmente a presença dos sintomas depressivos (Freitas et al, 2023).…”
Section: Discussionunclassified
“…Uma revisão de escopo mostrou que o maior comprometimento da qualidade de vida estava relacionado à demora no diagnóstico da doença, às reações hansênicas, incapacidades físicas, dor neuropática e estigma (Barcelos et al, 2021). Outro estudo avaliou a associação entre qualidade de vida e presença de sintomas de depressão, ansiedade e estresse em estudantes universitários da área da saúde, evidenciando que tais sintomas mostraram-se prevalentes e com impacto negativo na qualidade de vida dos estudantes, principalmente a presença dos sintomas depressivos (Freitas et al, 2023).…”
Section: Discussionunclassified
“…During the past and in recent years, the issue of MH and its relation to academic performance and QOL among students has been studied by many researchers [21,22]. Students' own beliefs might affect their MH status.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that especially during the first years of study, the QoL of students deteriorated and symptoms of anxiety and depressive disorders increased [ 16 , 17 ], which could mean that students are prone to develop mental disorders during their academic education. The study by Freitas et al [ 18 ] included 321 health students and found that there was a negative association between the quality of life and depression symptoms in all examined domains (physical and psychological well-being, social relations and environment), while anxiety symptoms showed a negative association in the environment domain, and stress symptoms had a negative association in the psychological domain. Furthermore, Alsubaie et al [ 19 ] found differences between students with and without depressive symptoms considering the psychological and social subscale of the WHOQoL-BREF.…”
Section: Introductionmentioning
confidence: 99%